Comparison of the effects of velocity-based vs. Traditional resistance training methods on adaptations in strength, power, and sprint speed: a systematic review, meta-analysis, and quality of evidence appraisal - Orange, S. T.; Hritz, A.; Pearson, L.; Jeffries, O.; Jones, T. W.; Steele, J. (Journal of Sports Sciences, 2022)
We estimated the effectiveness of using velocity feedback to regulate resistance training load on changes in muscle strength, power, and linear sprint speed in apparently healthy participants. Academic and grey literature databases were systematically searched to identify randomised trials that compared a velocity-based training intervention to a `traditional' resistance training intervention that did not use velocity feedback. Standardised mean differences (SMDs) were pooled using a random effects model. Risk of bias was assessed with the Risk of Bias 2 tool and the quality of evidence was evaluated using the GRADE approach. Four trials met the eligibility criteria, comprising 27 effect estimates and 88 participants. The main analyses showed trivial differences and imprecise interval estimates for effects on muscle strength (SMD 0.06, 95% CI -0.51-0.63; I2 = 42.9%; 10 effects from 4 studies; low-quality evidence), power (SMD 0.11, 95% CI -0.28-0.49; I2 = 13.5%; 10 effects from 3 studies; low-quality evidence), and sprint speed (SMD -0.10, 95% CI -0.72-0.53; I2 = 30.0%; 7 effects from 2 studies; very low-quality evidence). The results were robust to various sensitivity analyses. In conclusion, there is currently no evidence that VBT and traditional resistance training methods lead to different alterations in muscle strength, power, or linear sprint speed.